THE EFFECT OF GIVING PAPAYA SEED EXTRACT (Carica papaya L.) TROUGHT DRINKING WATER ON THE PERCENTAGE OF EXTERNAL OFFAL BROILER AGED 4 WEEKS - N.W.E.A., Wiriani; Dewi, G.A.M.K.; Wirawan, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of giving papaya seeds extract through drinking water on the external offal percentage of broiler aged 4 weeks. This research was conducted in Banjar Selanbawak Kelod, Selanbawak Village, Marga District, Tabanan Regency, Bali, which was carried out for 4 weeks. The experimental design used was a completely randomized design 318 with 4 treatments and 4 replications each there is 5 broilers, so that 80 bird total number of broilers was used. The treatments were broiler that were given drinking water without papaya seeds extract (PA/Control), 1% papaya seeds extract (PB), 2% papaya seeds extract (PC), 3% papaya seeds extract (PD). The variables observed were percentage of the head, neck, leg, blood, and feather. The results showed that the broilers who were given the treatment (PB), (PC), and (PD) of papaya seed extract through drinking water were not significantly different (P>0.05) to the treatment (PA/control) in the percentage of external offal broilers aged 4 weeks. From this research, it can be concluded that giving papaya seeds extract as much as 1%, 2%, and 3% in drinking water gives the same result external offal (head, neck, legs, blood, and feathers) percentage of broiler 4 weeks aged.